2020
DOI: 10.1038/s41598-020-59126-9
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide drift exposure leads to reduced herbicide sensitivity in Amaranthus spp.

Abstract: While the introduction of herbicide tolerant crops provided growers new options to manage weeds, the widespread adoption of these herbicides increased the risk for herbicide spray drift to surrounding vegetation. the impact of herbicide drift in sensitive crops is extensively investigated, whereas scarce information is available on the consequences of herbicide drift in non-target plants. Weeds are often abundant in field margins and ditches surrounding agricultural landscapes. Repeated herbicide drift exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 76 publications
0
21
1
1
Order By: Relevance
“…Empirical support for creeping resistance is provided by low-dose selection of experimental populations. Such studies, conducted with different species and different herbicides, have consistently demonstrated the ability of plants to evolve increased herbicide resistance (in some cases by many fold) after only two or three generations (176)(177)(178). That such a shift in herbicide response was due to the accumulation of multiple alleles was supported by a follow-up study on one of the selected populations that indicated at least three loci were involved.…”
Section: Genetics Of Herbicide Resistancementioning
confidence: 93%
“…Empirical support for creeping resistance is provided by low-dose selection of experimental populations. Such studies, conducted with different species and different herbicides, have consistently demonstrated the ability of plants to evolve increased herbicide resistance (in some cases by many fold) after only two or three generations (176)(177)(178). That such a shift in herbicide response was due to the accumulation of multiple alleles was supported by a follow-up study on one of the selected populations that indicated at least three loci were involved.…”
Section: Genetics Of Herbicide Resistancementioning
confidence: 93%
“…Dicamba use is on an upwards trajectory in agriculture due to the adoption of dicamba-tolerant crops (USDA- ERA, 2018). However, this herbicide can drift to non-target areas, causing significant damage to unprotected crops and natural plant populations (Egan et al 2014, Bohnenblust et al 2016, Jones et al 2018, Vieira et al 2020). Currently, we understand little about how the widespread use of dicamba may impact non-target organisms and even less about whether dicamba drift may impact plant-insect interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A broad expectation is that exposure to a synthetic auxin, such as dicamba, could alter plant allocation towards growth and defence, and potentially lead to increased vulnerability to herbivores, in line with growth-defense tradeoff framework (Coley, Bryant, Chapin 1985). Recent work has shown that exposure to drift rates of herbicides like dicamba can lead to the evolution of reduced herbicide sensitivity (Vieria et al 2020) and recurrent selection of low dose herbicides can lead to nontarget site resistance (Busi et al 2013), however there is little understanding of how this process may influence selection for allocation herbivory defense.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide drift to roadsides and field borders caused by application miscues has led to the evolution of herbicide resistance within two generations of Amaranthus spp. (Vieira et al 2020). As a result, focus should be placed on using precise application procedures to maximize efficacy of herbicide applications while maintaining environmental safety (Matthews et al 2014).…”
Section: Introductionmentioning
confidence: 99%